APPARATUS HR COMPETENCY IMPROVEMENT THROUGH UTILIZATION OF INFORMATION AND COMMUNICATION TECHNOLOGY - R. Taqwaty Firdausijah (INFOKUM, 2021)
This study aims to investigate and analyze the impact of the use of Information and Communication Technology (ICT) on increasing the competency of Human Resources (HR) of personnel in an organization. Improving the competence of HR apparatus is a crucial factor in dealing with changes in an increasingly dynamic and complex work environment. This research uses a qualitative descriptive approach. The results of the study show that the use of Information and Communication Technology (ICT) in increasing the competence of State Civil Apparatus (ASN) human resources is very important to support e-Government transformation and improve the quality of public services. Through ICT training, ASN can learn independently, collaborate effectively, and manage personnel information more efficiently. With planned preparation, maturation, consolidation, and utilization stages, ICT training systematically increases ASN competence in dealing with information and communication technology challenges in a modern public service environment.